PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE JIGSAW BERBANTU PAMFLET TERHADAP HASIL BELAJAR IPS TERPADU PESERTA DIDIK KELAS VIII MTs AN-NUR PELOPOR BANDAR JAYA TAHUN PELAJARAN 2018/2019 - Andre Nur Wicaksono; Triani Ratnawuri; Meyta Pritandhari (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2021)
Learning process in MTs AN-NUR Pelopor Bandarjaya is still many who use conventional learning models so that students do not think critically and independently. The students only receive information from the teacher without any intention to develop or seek knowledge by themselves and there are still many students who have not completed the learning outcomes of Integrated IPS Class VIII MTs AN-NUR Pelopor Bandarjaya. With the existence of alternative learning models that can influence learning outcomes by using Jigsaw Cooperative Learning Type Model Pamphlet-assisted, it is expected to be a suggestion / input to the teacher so that classroom learning is more effective by using the Jigsaw Cooperative Learning Type Model Pamphlet-assisted. The aim of the research is to increase the Integrated IPS Outcomes of Class VIII Students of MTs AN-NUR Pelopor Bandarjaya Academic Year 2018/2019. The researcher uses the experimental method (Quasi Experimental), with the form of experimental design that is the form of The Non-Equivalent Control Group Design. The result of hypothesis analysis the value of tcount ˃ ttable at the significance level of 5% is 4.78> 1.72. Students are declared complete with KKM 65 as many as 18 students or with a percentage of 75%, while students in the unfinished category as many as 6 students with a percentage of 25%. Thus it shows that there is a positive influence on the use of the Jigsaw Cooperative Learning Type Model Pamphlet-assisted toward Integrated IPS Outcomes of Class VIII Students in MTs AN-NUR Pelopor Bandarjaya